Screening and Evaluation of Potential Efflux Pump Inhibitors with a Seaweed Compound Diphenylmethane-Scaffold against Drug-Resistant Escherichia coli - Lu, Wen-Jung; Lian, Yu-Wei; Chang, Chun-Ju; Lin, Hsuan-Ju; Huang, Chian-Yun; Hsu, Pang-Hung; Lin, Hong-Ting (Antibiotics (Basel), 2024)
Drug-resistant efflux pumps play a crucial role in bacterial antibiotic resistance. In this study, potential efflux pump inhibitors (EPIs) with a diphenylmethane scaffold were screened and evaluated against drug-resistant Escherichia coli. Twenty-four compounds were docked against the drug-binding site of E. coli multidrug transporter AcrB, and 2,2-diphenylethanol (DPE), di-p-tolyl-methanol (DPT), and 4-(benzylphenyl) acetonitrile (BPA) were screened for their highest binding free energy. The modulation assay was further used for EPI evaluation, revealing that DPE, DPT, and BPA could reduce the drug IC50 value in E. coli strains overexpressing AcrB, indicating their modulation activity. Only DPE and BPA enhanced intracellular dye accumulation and inhibited the efflux of ethidium bromide and erythromycin. In addition, DPE and BPA showed an elevated post-antibiotic effect on drug-resistant E. coli, and they did not damage the permeability of the bacterial outer membrane. The cell toxicity test showed that DPE and BPA had limited human-cell toxicity. Therefore, DPE and BPA demonstrate efflux pump inhibitory activity, and they should be further explored as potential enhancers to improve the effectiveness of existing antibiotics against drug-resistant E. coli.